2021
DOI: 10.1002/onco.13889
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Cell-Free DNA Genotyping: From an Emerging Concept to a Standard-of-Care Tool in Metastatic Non-Small Cell Lung Cancer

Abstract: Plasma cell-free DNA (cfDNA) genotyping is an alternative to tissue genotyping particularly when tissue specimens are insufficient or unavailable and provides critical information that can be used to guide treatment decisions in managing patients with non-small cell lung cancer (NSCLC). In this article, we review the evolution of plasma cfDNA genotyping from an emerging concept, through development of analytical methods, to its clinical applications as a standard-of-care tool in NSCLC.The number of driver or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“… 31 Currently, US FDA-approved companion diagnostics are Guardant360 ® CDx (Guardant, California, CA) and FoundationOne ® Liquid CDx (Foundation Medicine, Cambridge, MA). 98 Other detection methods, such as Sanger sequencing, RNA sequencing, direct sequencing and mass spectroscopy, are alternative options that are less commonly used. 17 …”
Section: Detection Of Egfr Exon 20 Insertion Mutat...mentioning
confidence: 99%
“… 31 Currently, US FDA-approved companion diagnostics are Guardant360 ® CDx (Guardant, California, CA) and FoundationOne ® Liquid CDx (Foundation Medicine, Cambridge, MA). 98 Other detection methods, such as Sanger sequencing, RNA sequencing, direct sequencing and mass spectroscopy, are alternative options that are less commonly used. 17 …”
Section: Detection Of Egfr Exon 20 Insertion Mutat...mentioning
confidence: 99%
“…Thus, current clinical guidelines recommend cfDNA testing for the detection of molecular alterations in NSCLC, either in treatment-naïve patients or in patients who progressed to EGFR TKIs [ 141 ]. EGFR- mutant NSCLC constitutes one of the major paradigms of integrating liquid biopsy testing in the clinical setting that is validated through the liquid biopsy tests already approved by the FDA [ 142 ].…”
Section: Liquid Biopsy Testing In Nsclcmentioning
confidence: 99%
“…Jin et al were able to identify miR-181-5p, miR-30a-3p, miR-30e-3p and miR-361-5p as being specific for adenocarcinoma, and miR-10b-5p, miR-15b-5p and miR-320b for SCLC (small cell lung cancer) [62]. In addition, taking advantage of the many benefits of NGS, oncology researchers have developed liquid biopsy testing for lung cancer diagnosis [63]. Leighl et al observed a very high concordance for NGS results from cfDNA and tissue DNA in untreated metastatic NSCLC [64].…”
Section: Ngs In Lung Cancer Diagnosismentioning
confidence: 99%
“…NGS testing was successfully recommended in lung cancer diagnosis by different expert panels [66] and oncology organizations [67]. Gray et al performed a thorough survey of the relevant literature regarding liquid biopsy and observed that the advantages of NGS have helped to develop different assays using liquid biopsy samples for the early diagnosis, treatment selection, minimal disease detection, monitoring treatment efficacy and evaluation of tumor burden in lung cancer [63]. Sueoka-Aragane et al observed that the analysis of ctDNA by NGS could be a promising tool for the evaluation of the efficacy of osimertinib in NSCLC with EGFR T790M mutation [68].…”
Section: Ngs In Lung Cancer Diagnosismentioning
confidence: 99%